Competitividad del Departamento del Meta Frente al Tlc con Europa (2013)
Market globalization is inevitable, therefore Meta department must be prepared, and the European market is attractive but is going through difficult times economically. The Meta has significant comparative advantages of location and territory, with ample opportunities to generate competitive advantages of industrial investment and diversification of agricultural products. What you may do with linking the Government, private enterprise and academia.